Hazard Analysis Critical Control Points (HACCP) Principle 2: Determine Critical Control Points (CCPs) - Ronald H. Schmidt; Debby L. Newslow (EDIS)
FSHN07-04, a 5-page factsheet by Ronald H. Schmidt and Debby Newslow, explains the process of determining Critical Control Points in a HACCP system. Includes a helpful decision tree. Published by the UF Department of Food Science and Human Nutrition, July 2007.